STATUS ANTROPOMETRI DENGAN BEBERAPA INDIKATOR PADA MAHASISWA TPB-IPB - Yunieswati, Wilda; Briawan, Dodik (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The objective of this study was to analyze the anthropometry status, and body fat percentage of first year students in IPB. The subjects of this study were 117 IPB first year students. The result shows that most of the male subjects has a normal body mass index (75.0%), normal waist circumference (87.5%) and normal waist-hip-ratio (93.8%). Most of the male subjects has a normal body fat percentage (37.5%). In the meanwhile, most of the female subjects has normal body mass index (83.2%), normal waist circumference (98.0%) and normal waist-hip-ratio (95.0%). Most of the female subjects had a normal body fat percentage (56.0%). There was a significant correlation between body mass index, waist circumference, waist hip ratio, and percentage of body fat (p<0.05).